A history of the Pacific Islands - Fischer, Steven R. (Palgrave essential histories, 2013)
This study of the Pacific Islands provides a dynamic and provocative account of the peopling of the Pacific, and its broad impact on world history. Spanning nearly 50,000 years of human presence in an area which comprises one-third of our planet - Melanesia, Micronesia and Polynesia - the narrative follows the development of the region, from New Guinea's earliest settlement to the creation of the modern Pacific states. -Publlishers Description